2017
DOI: 10.1371/journal.pone.0177883
|View full text |Cite
|
Sign up to set email alerts
|

Detecting early signs of heat and drought stress in Phoenix dactylifera (date palm)

Abstract: Plants adapt to the environment by either long-term genome evolution or by acclimatization processes where the cellular processes and metabolism of the plant are adjusted within the existing potential in the genome. Here we studied the adaptation strategies in date palm, Phoenix dactylifera, under mild heat, drought and combined heat and drought by transcriptomic and metabolomic profiling. In transcriptomics data, combined heat and drought resembled heat response, whereas in metabolomics data it was more simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 56 publications
8
46
0
Order By: Relevance
“…The major GO networks involved those related to cell wall related biogenesis and metabolism (GO: 0009834 and GO: 0044036), small molecule related biosynthetic and metabolic processes (ath00940, GO: 0009698, GO: 0044283 and GO: 0010565) and ion transport and homeostasis related processes (GO: 0006811, GO: 0034220 and GO: 0030004). These data imply that genes in these networks are more extensively induced to differentially express to respond to drought stress [25,30,31]. We further investigated the enriched KEGG pathways and found that the functions of the enriched pathways were generally consistent with that of the enriched GO terms as shown above ( Supplementary Table S5).…”
Section: Ontology Enrichment Analysis Of Genes Responding To Drought supporting
confidence: 58%
“…The major GO networks involved those related to cell wall related biogenesis and metabolism (GO: 0009834 and GO: 0044036), small molecule related biosynthetic and metabolic processes (ath00940, GO: 0009698, GO: 0044283 and GO: 0010565) and ion transport and homeostasis related processes (GO: 0006811, GO: 0034220 and GO: 0030004). These data imply that genes in these networks are more extensively induced to differentially express to respond to drought stress [25,30,31]. We further investigated the enriched KEGG pathways and found that the functions of the enriched pathways were generally consistent with that of the enriched GO terms as shown above ( Supplementary Table S5).…”
Section: Ontology Enrichment Analysis Of Genes Responding To Drought supporting
confidence: 58%
“…Some of the differentially expressed genes that were downregulated under drought included ribulose-1,5bisphosphate, carboxylase/oxygenase, oxygen-evolving enhancer protein 2, chloroplastic-like, and cytochrome P450 implying the deactivation of the photosynthetic pathways in response to the treatment conditions. Safronov et al (2017) used transcriptomic and metabolomic profiling to characterize the response to heat and drought stress in P. dactylifera ( Table 1). The two stresses had similar effects including the upregulation of soluble carbohydrates and increased antioxidant activity in the cytosol, chloroplasts, and peroxisomes.…”
Section: Omic Studies Of Water Shortage In Date Palmmentioning
confidence: 99%
“…In the last few years, a number of studies have reported variation in the response to abiotic stresses among cultivars and their seedling progeny (Alhammadi and Edward, 2009;Al Kharusi et al, 2017;Al-Khateeb et al, 2019). Others have begun to probe the complex responses to abiotic stresses using genome-wide omic technologies such as transcriptomics, proteomics, methylomics, and metabolomics (Yaish and Kumar, 2015;Safronov et al, 2017;Yaish et al, 2017;Al-Harrasi et al, 2018;Rikek et al, 2019). Other recent developments include advances in transformation strategies for genetic engineering and gene editing (Prieto, 2011;Cardi et al, 2017), use of heterologous expression systems for studies of gene function (Patankar et al, 2019a,b), improvements to the date palm genome (Hazzouri et al, 2019), and demonstration of genome-wide association studies (GWAS) for mapping phenotypic trait variation in date palm (Hazzouri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The shift to soluble sugar, secondary metabolite production and activation of ROS eliminating processes in response to drought were the most noticeable results of this work. In the non-model plant, Phoenix dactylifera (date palm), heat and drought stresses induced carbohydrate metabolism and cell wall biogenesis (Safronov et al 2017). Drought stress response and photorespiration was also studied by metabolomic approaches in maize (Obata et al 2015) and in sorghum (Ogbaga et al 2016).…”
Section: Metabolomics and Stress Responses In Crop Plant Speciesmentioning
confidence: 99%